Rotavirus Enterotoxin NSP4 Has Mucosal Adjuvant Properties - Kavanagh, Owen V. (2010)
Rotavirus nonstructural protein 4 (NSP4) is a protein with pleiotropic properties. It functions in rotavirus morphogenesis, pathogenesis, and is the first described viral enterotoxin. Since many bacterial toxins function as potent mucosal adjuvants, we evaluated whether baculovirus-expressed recombinant simian rotavirus SA11 NSP4 possesses adjuvant activity by co-administering NSP4 with keyhole limpethemocyanin (KLH), tetanus toxoid (TT) or ovalbumin (OVA) as model antigens in mice. Following intranasal immunization, NSP4 significantly enhanced both systemic and mucosal immune responses to model immunogens, as compared to the control group, in an antigen-specific manner. Both full-length and a cleavage product of SA11 NSP4 had adjuvant activity, localizing this activity to the C-terminus of the protein. NSP4 forms from virulent and avirulent porcine rotavirus OSU strain, and SA11 NSP4 localized withina 2/6 -virus like particle (VLP) also exhibited adjuvant effects. These studies suggest that the rotavirus enterotoxin NSP4 can function as an adjuvant to enhance immune responses for a co-administered antigen.